Association of biomarker and physiologic indices with mortality in older adults: Cardiovascular Health Study. - Sanders, Jason L; Arnold, Alice M; Boudreau, Robert M; Hirsch, Calvin H; Kizer, Jorge R; Kaplan, Robert C; Cappola, Anne R; Cushman, Mary; Jacob, Mini E; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2018)
Background: A goal of gerontology is discovering aging phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers strongly and independently associated with mortality and which statistically attenuate chronologic age could be used to define such a phenotype. We determined the association of a Biomarker Index (BI) with mortality and compared it to a validated Physiologic Index (PI) in older adults. Methods: The indices were constructed in the Cardiovascular Health Study, mean (SD) age 74.5 (5.1) years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor (IGF)-1, IGF binding protein 3, amino-terminal pro-B-type natriuretic peptide, dehydroepiandrosterone sulfate, and interleukin-6, and was built in test (N=2197) and validation (N=1124) samples. The PI included carotid intima-media thickness, pulmonary capacity, brain white matter grade, cystatin-C, and fasting glucose. Multivariable Cox proportional hazards models predicting death were calculated with 10 years of follow-up. Results: In separate age-adjusted models, the hazard ratio (HR) for mortality per point of the BI was 1.30 (95% CI 1.25, 1.34) and the BI attenuated age by 25%. The HR for the PI was 1.28 (1.24, 1.33) (29% age attenuation). In the same model, the HR for the BI was 1.23 (1.18, 1.28) and for the PI was 1.22 (1.17, 1.26), and age was attenuated 42.5%. Associations persisted after further adjustment. Conclusions: The BI and PI were significantly and independently associated with mortality. Both attenuated the age effect on mortality substantially. The indices may be feasible phenotypes for developing interventions hoping to alter the trajectory of aging.